2008
DOI: 10.1002/prot.21945
|View full text |Cite
|
Sign up to set email alerts
|

MUSTER: Improving protein sequence profile–profile alignments by using multiple sources of structure information

Abstract: We develop a new threading algorithm MUSTER by extending the previous sequence profile–profile alignment method, PPA. It combines various sequence and structure information into single-body terms which can be conveniently used in dynamic programming search: (1) sequence profiles; (2) secondary structures; (3) structure fragment profiles; (4) solvent accessibility; (5) dihedral torsion angles; (6) hydrophobic scoring matrix. The balance of the weighting parameters is optimized by a grading search based on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
308
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 66 publications
1
308
0
Order By: Relevance
“…4(b)]. 50 The homology modeling was based on protein NLRX1 that shares 24.1% sequence identity with CLLR2. NLRX1, also known as NOD9, is a mitochondrial protein thought to be involved in an antiviral immune response against viral ribonucleic acid (RNA).…”
Section: Secondary Structurementioning
confidence: 99%
“…4(b)]. 50 The homology modeling was based on protein NLRX1 that shares 24.1% sequence identity with CLLR2. NLRX1, also known as NOD9, is a mitochondrial protein thought to be involved in an antiviral immune response against viral ribonucleic acid (RNA).…”
Section: Secondary Structurementioning
confidence: 99%
“…In CAFASP [22] and the recent CASP Server Section [23•], several sequence-profile-based methods were ranked at the top of single-threading servers. Wu and Zhang [24] recently showed that the accuracy of the sequence PPAs can be further improved by about 5-6% by incorporating a variety of additional structural information.…”
Section: Template Structure Identificationmentioning
confidence: 99%
“…For this purpose, we tested LOMETS (LOcal MEtaThreading-Server [114]), a webserver that uses 8 different methods and ranks the results. Table I summarizes the different results obtained for MUSTER [115], SAM [116], PROSPECT2 [117], SP3 [118], PPA-I, HHsearch [119], SPARKS2 [120], and FUGUE [121]. The three first methods provide structural models with a medium confidence rate while the models constructed with the last methods are associated with a low confidence index.…”
Section: Building Structural Modelsmentioning
confidence: 99%